The Evolution in Value Relevance of Accounting Measures in Indonesia - Eko Suwardi (Gadjah Mada International Journal of Business, 2020)
This paper utilizes the model of share price, which is derived from the valuation model of residual income, to rigorously assess the evolution of value relevance of accounting measures in Indonesia, an emerging market country which has its landscape of equity valuation changed substantially. Using two different approaches, cross sectional and panel regressions, the results indicates a strong linear association between share price and accounting measures. Cross-sectional yearly price regressions provide a strong evidence of non-linear changes on the value relevance of accounting measures over time.  Moreover, using panel data analysis, the results of unconditional comparison tests reveal that that the increased value-relevance of the balance sheet would be offset by a reduction of the value-relevance of earnings per share during IFRS regime. It could potentially contribute to explain the decrease in value relevance of accounting numbers during the switchover to IFRS in Indonesia.